Myocardial myostatin in spontaneously hypertensive rats with heart failure. (15th July 2016) - Damatto, R.L.; Lima, A.R.R.; Martinez, P.F.; Cezar, M.D.M.; Okoshi, K.; Okoshi, M.P.
Abstract: Background: Myostatin has been shown to regulate skeletal and cardiac muscle growth. However, its status on long-term hypertrophied myocardium has not been addressed. The purpose of this study was to evaluate the expression of myocardial myostatin and its antagonist follistatin in spontaneously hypertensive rats (SHR) with heart failure. Methods: Eighteen-month-old SHR were evaluated to identify clinical features of heart failure such as tachypnea/labored respiration and weight loss. After heart failure was detected, rats were subjected to echocardiogram and euthanized. Age-matched normotensive Wistar-Kyoto (WKY) rats were used as controls. Myostatin and follistatin protein expression was assessed by Western blotting. Statistical analysis was performed by Student's t test. Results: All SHR (n = 8) presented right ventricular hypertrophy and five had lung congestion. SHR had left chambers hypertrophy and dilation (left atrial diameter: WKY 5.73 ± 0.59; SHR 7.28 ± 1.17 mm; p = 0.004; left ventricular (LV) diastolic diameter/body weight ratio: WKY 19.6 ± 3.1; SHR 27.7 ± 4.7 mm/kg; p = 0.001), and LV systolic dysfunction (midwall fractional shortening: WKY 34.9 ± 3.31; SHR 24.8 ± 3.20%; p = 0.003). Myocyte diameter (WKY 23.1 ± 1.50, SHR 25.5 ± 1.33 μm; p = 0.004) and myocardial interstitial collagen fraction (WKY 4.86 ± 0.01; SHR 8.36 ± 0.02%; p < 0.001) were increased in the SHR. Myostatin (WKY 1.00 ± 0.16; SHR 0.77 ± 0.23 arbitrary units; p = 0.035) and follistatin (WKY 1.00 ± 0.35; SHR 0.49 ± 0.18 arbitrary units; p = 0.002) expression was lower in SHR. Myostatin and follistatin expression negatively correlated with LV diastolic diameter-to-body weight ratio and LV systolic diameter, and positively correlated with midwall fractional shortening. Conclusion: Myostatin and follistatin protein expression is reduced in the long-term hypertrophied myocardium from spontaneously hypertensive rats with heart failure.